The Influence of Using Online Visual Merchandising on Attitude Towards Uniqlo E-Commerce and Its Impact on Purchase Intention - Dian Puspitasari; Mario Adilson Febiyando; Adellia Anjani Hartono; Artha Sejati Ananda (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2026)
The rapid growth of e-commerce has transformed consumer shopping behaviour, particularly in the fast-fashion industry, making online visual merchandising (OVM) a critical factor influencing consumer evaluations and purchase decisions. This study examines the effect of OVM on consumers’ attitudes toward the Uniqlo e-commerce platform and its impact on purchase intention using the Stimulus–Organism–Response (S-O-R) framework. In this model, OVM dimensions act as stimuli, consumer attitude represents the organism, and purchase intention constitutes the behavioural response. Data were collected from 314 Indonesian consumers aged 18–35 years who had previously accessed the Uniqlo website or mobile application. The data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results show that Colour positively influences consumer attitude (β = 0.182, p = 0.029), while Product Presentation has a stronger positive effect (β = 0.190, p = 0.004). Consumer attitude also significantly enhances purchase intention (β = 0.338, p < 0.001). These findings indicate that product-related visual information is more influential than general platform aesthetics in shaping favourable consumer attitudes and purchase intentions within fast-fashion e-commerce environments.